INFLUÊNCIA DA CULTURA ORGANIZACIONAL NA FORMAÇÃO DA IDENTIDADE DOS INDIVÍDUOS NAS ORGANIZAÇÕES: UM ESTUDO COM GERENTES DO SETOR BANCÁRIO DE SÃO PAULO - TOMÉ, ALEXANDRE SCHERRER (2016)
This study aims to understand the importance of the elements of organizational culture and how each contributes to the process of individual identity formation, in this specific case, the bank manager, the leader of a team. This work had its theoretical basis rooted in the concepts of organizational culture, and in the formation and identity construction process, relative to its formation, construction and demonstration. From its theoretical relevance, this paper intends to bring to the academic community significant contributions about organizational culture and identity construction studies. It was chosen the qualitative-exploratory research approach for the elaboration of this work. The study instrument used in this research was script based semi structured interview. From the data obtained through interviews with seven bank managers of the State of São Paulo properly guided and supported by theoretical support, based on the following categories: Managers identity profiles, Organizational identification, the Teamwork and identity formation. Based on this effort, it was noticed the manager’s need to take a commercial identity for himself, and the finding that after becoming managers, the discretion and the responsibility and the discipline were some of the aspects that had a bigger impact on their lives. Another important result was the possibility of characterizing the forming elements of professional identity from the organizational culture elements relative to its influence in the exercise in the management activities, as in the norms, rules, values, rites, rituals and ceremonies, and lastly, the evidence of the importance of organizational culture on the formation of identity in the manager’s performance.